Kristenisasi di Pulau Dewata pada Era Kolonial Belanda - Tri Wahyuning M. Irsyam (Department of History, Faculty of Humanities, Diponegoro University, 2018)
This article discusses Christianization in Bali during the late XIX until XX century that was not only become religious phenomena, but also the pragmatical of government policy. It is compiled with historical method. According to the study, it can be delivered that Bali in the Dutch colonial era was in a tense situation. It was not only because the new religion came from the other parts of the world and therefore considered as alien by the local community based on Hinduism, but also discrimination against the zending institution conducted by the colonial regime. In the macro policy level, the government put into zending and mission became counterpart as well as media to conquer and civilize the colonies in order to face of Islamic radicalism as a common enemy. However, the government viewed that Bali as a strategic partner against the common enemy. Christianization was feared to lead a strong rejection from the Balinese people and ultimately led to resistance of the government. Therefore, the government prohibited zending in Bali despite the reasons that were not commonly found in the dominant politics of cultural preservation.